Risk-Based Tax Compliance: Analisis Penerapan Manajemen Risiko dalam Pengelolaan Kewajiban Pajak Perusahaan - Purwantini, Heni; Hasibuan, Reza Rahmadi (Awatara Publisher, 2025)
This study examines the implementation of risk management in corporate tax obligations using a risk-based tax compliance approach. Companies face complex transactions, regulatory changes, and intensified tax oversight, increasing the potential for reporting errors. The study employs a qualitative exploratory method, including in-depth interviews, observations, and internal document analysis, to understand risk identification, mapping, mitigation, and internal control processes. Findings indicate that companies systematically identify risks, use risk matrices to prioritize control measures, and strengthen mitigation procedures through multilayer verification and digital technology utilization. Internal coordination, structured documentation, and employee training are key factors in successful implementation. The application of risk management not only reduces audit findings and reporting errors but also fosters a sustainable compliance culture. This study contributes theoretically by expanding the literature on risk-based tax compliance and provides practical implications for companies to develop adaptive and systematic compliance strategies.